Advocating the Role of Disabled Artists from the Artistic Ecosystem to the Spectrum of Karawitan Performances - Swara, Lintang Pramudia; Listiowati, Nensi; Pardosi, Gilbert Natanael; de Fretes, Daniel (Institut Seni Indonesia Yogyakarta, 2023)
This research aims to uncovering the experiences of individuals withdisabilities within the spectrum of karawitan. Their contributions are highlightedthrough captivating performances at the Yogyakarta Gamelan Festival 2022. Disabledfriends successfully presented works that express and actualize their roles withinsociety, including within the artistic ecosystem. The research aims to explore theexperiences interpreted by disabled individuals from Sanggar Seni Candrika Adikara.We chose a case study as the primary approach for the qualitative method thatunderlies this research. The case study involved observing Sanggar Seni CandrikaAdikara and engaging in dialogue with key figures involved in the intersection of the artworld and disability issues in Yogyakarta and its surroundings. Our study wasexpanded by exploring the realms of literary and visual arts and reclaiming performingarts with a fresh discourse on self-equality. The participants' perspectives become asignificant force of value that is unveiled and presented to the readership and theacademic community. The articulation of the artistic experiences of our disabledfriends becomes a manifestation of the creation of a new paradigm that prioritizestheir needs for existence and recognition in various aspects of life.